The inequity of conscientious objection: Refusal of emergency contraception - Yang, Chelsey (Nursing ethics, 2020)
In the medical field, conscientious objection is claimed by providers and pharmacists in an attempt to forgo administering select forms of sexual and reproductive healthcare services because they state it goes against their moral integrity. Such claim of conscientious objection may include refusing to administer emergency contraception to an individual with a medical need that is time-sensitive. Conscientious objection is first defined, and then a historical context is provided on the medical field’s involvement with the issue. An explanation of emergency contraception’s physiological effects is provided along with historical context of the use on emergency contraception in terms of United States Law. A comparison is given between the United States and other developed countries in regard to conscientious objection. Once an understanding of conscientious objection and emergency contraception is presented, arguments supporting and contradicting the claim are described. Opinions supporting conscientious objection include the support of moral integrity, religious diversity, and less regulation on government involvement in state law will be offered. Finally, arguments against the effects of conscientious objection with emergency contraception are explained in terms of financial implications and other repercussions for people in lower socioeconomic status groups, especially people of color. Although every clinician has the right and responsibility to treat according to their sense of responsibility or conscience, the ethical consequences of living by one’s conscience are limiting and negatively impact underprivileged groups of people. It is the aim of this article to advocate against the use of provider’s and pharmacist’s right to claim conscientious objection due to the inequitable impact the practice has on people of color and individuals with lower incomes.